A Surgical View of Anatomy: Perspectives from Students and Instructors. Issue 1 (11th July 2020) - Dee, Edward Christopher; Alty, Isaac G.; Agolia, James P.; Torres‐Quinones, Carlos; van Houten, Trudy; Stearns, Dana A.; Lillehei, Craig W.; Shamberger, Robert C.
Abstract : As curricular emphasis on anatomy in undergraduate medical education continues to evolve, new approaches to anatomical education are urgently needed to prepare medical students for residency. A surgical anatomy class was designed for third‐ and fourth‐year medical students to explore important anatomical relationships by performing realistic surgical procedures on anatomical donors. Under the guidance of both surgeons and anatomists, students in this month‐long elective course explored key anatomical relationships through performing surgical approaches, with the secondary benefit of practicing basic surgical techniques. Procedures, such as left nephrectomy, first rib resection for thoracic outlet syndrome, and carotid endarterectomy, were adapted from those used clinically by multiple surgical subspecialties. This viewpoint commentary highlights perspectives from students and instructors that suggest the value of a surgical approach to anatomical education for medical students preparing for procedure‐oriented residencies, with the goals of: (1) describing the elective at the authors' institution, (2) promoting similar efforts across different institutions, and (3) encouraging future qualitative and quantitative studies of similar pedagogic efforts.